Species survey of the subfamily Cerambycinae (Coleoptera: Cerambycidae) in the Rio Doce State Park, Minas Gerais, Brazil - Corrêa, Carlos A.; Migliore, Letizia J.; Garbelini, Luan; Zanuncio, José C.; Ribeiro, Sérvio P. (Zootaxa, 2020)
The Rio Doce State Park (“PERD”) is the largest Atlantic Forest remnant in Minas Gerais State, Brazil, with predominantly semi-deciduous forests. The longhorned beetles of the Cerambycinae subfamily (Coleoptera: Cerambycidae) are distributed worldwide, developing on healthy, stressed or recently dead trees. Faunistic surveys are necessary to understand about the Minas Gerais’ cerambycid fauna due to a lack of research, especially in the eastern region of the state. A list of species of the subfamily Cerambycinae (Coleoptera: Cerambycidae), collected in the PERD during the rainy season (September 2013- February 2014), is presented. The beetles were collected using a light trap and through their emergence from Anadenanthera colubrina (Vell.) Brenan (Fabaceae) logs. A total of 663 individuals of 33 species, 30 genera, and 15 tribes of the Cerambycinae subfamily were collected. The species Malacopterus tenellus (Fabricius, 1801) was registered for the first time in Minas Gerais State, while A. colubrina is a new host plant for 14 Cerambycinae species. The geographical distribution, number of host plants and materials examined are presented for each species collected. This is the first list of Cerambycidae species from the Rio Doce State Park.